Interference of mother tongue (L1) in the English translation materials - Subramaniam, Vijayaletchumy; Dani, Noor Aina; Daing Melebek, Abdul Rashid; Wan Mohammad, Wan Muna Ruzanna (Center for Promoting Ideas, 2011)
Malaysian philosophy, purpose and objective of the education system is rooted and based on policies stated in the National Education Policy 1956 and Education Act 1961. Whereas the Education Ordinance 1952 urged all Chinese and Tamil schools to be given equal opportunity to learn English and Malay language together with their mother tongue. This policy has open up opportunity to the non-Bumis to learn their mother tongue without any fixed rules. The learning of mother tongue was not only limited to the basic level, but it continues to the university level. The findings of this research is important especially in the teaching of Malay language as the medium of instruction in the education system. All these three parties the Ministry of Education, Translation Institute and Ministry of Higher Education play important roles in producing the quality translation materials.